2017
DOI: 10.1016/j.celrep.2017.09.086
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Variant H2A.Z Is a Master Regulator of the Epithelial-Mesenchymal Transition

Abstract: Epithelial-mesenchymal transition (EMT) is a profound example of cell plasticity that is crucial for embryonic development and cancer. Although it has long been suspected that chromatin-based mechanisms play a role in this process, no master regulator that can specifically regulate EMT has been identified to date. Here, we show that H2A.Z can coordinate EMT by serving as either an activator or repressor of epithelial or mesenchymal gene expression, respectively. Following induction of EMT by TGF-β, we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Positive enhanced correlation between H2A.ZK101me2 with SMYD3 has been observed in human breast tissue biopsies [90]. However contradicting role of H2A.Z has also been reported recently by Domaschenz et al 2017 [87]. They confirmed that H2A.Z depletion imitates the EMT condition that is being produced by TGF-β pathway induction whereas overexpression induce the epithelial genes [87].This study could be further supported by the fact that loss in H2A.Z in MCF-10A cell line, EMT was induced ( Fig.…”
Section: H2a Familymentioning
confidence: 79%
See 2 more Smart Citations
“…Positive enhanced correlation between H2A.ZK101me2 with SMYD3 has been observed in human breast tissue biopsies [90]. However contradicting role of H2A.Z has also been reported recently by Domaschenz et al 2017 [87]. They confirmed that H2A.Z depletion imitates the EMT condition that is being produced by TGF-β pathway induction whereas overexpression induce the epithelial genes [87].This study could be further supported by the fact that loss in H2A.Z in MCF-10A cell line, EMT was induced ( Fig.…”
Section: H2a Familymentioning
confidence: 79%
“…H2A.Z H2A.Z histone variant was for the first time reported by West and Bonner, 1980 [86]. It is encoded by two genes H2A.Z1 and H2A.Z2 [87]. Although H2A.Z accounts for only 5% of the total H2A canonical histones, it is expressed throughout the entire cell cycle [88].…”
Section: H2a Familymentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, for 5 expressed H2A.Z, only one H2A.Z (Zm00001d027760) was in module II, and the remaining 4 H2A.Z were distributed in four different modules (I-C,11,16, and 18; Supplemental Data Set 4). The high variation of expression patterns for different H2A.Z genes is in line with the diverse functions of H2A.Z variants, including DNA repair, apparently contradictory roles in gene activation and silencing, nucleosome turnover, heterochromatin, boundary element, and chromatin fiber formation (Zlatanova and Thakar, 2008;Altaf et al, 2009;Dai et al, 2017;Domaschenz et al, 2017).…”
Section: Genes Expressed During the Coenocyte Formation Stage (Stage Ii)mentioning
confidence: 88%
“…LMO4 (LIM domain only 4) has been shown to be an essential cofactor in EMT at least in neuroblastoma and neural crest cells [62]. ANP32E (Acidic nuclear phosphoprotein 32 family member E) is a histone chaperone that mediates removal of histone H2A.Z from the nucleosome [63], and it has been shown that H2A.Z is a master regulator of EMT [64]. TGFB1I1 (Transforming growth factor beta 1 induced transcript 1) is a coactivator of the androgen receptor, it is known to be associated with prostate cancer, and it can induce EMT, at least in astrocytomes.…”
Section: Specific Gene Clusters and Individual Genesmentioning
confidence: 99%